Representing the Rural: New Rural Imaginaries on the English Stage since 2000 - Edwards, Gemma (2021)
This thesis explores the representation of the English rural in contemporary theatre and performance. Here, I make the case that while a survey of theatre since 2000 evidences a relatively healthy engagement with the rural across a range of English stages, these plays and performances tend to be sidelined in contemporary theatre studies. In the pages that follow, I seek to address this neglect by affording the representation of the rural a central critical focus, with the aim of demonstrating the ways in which plays about the rural are both contemporary and political, making for a rich and stimulating object of study.